Case Report on Wilson's Disease: An Unusual Presentation - Azad, KAK; Sardar, Md H; Hasan, A; Saleh, MA; Akter, N; Bahar, T; Paul, SK; Hossain, MZ (Bangladesh Medical Journal, 2011)
Key Words: Wilson's Disease; Neuropsychiatric disorder; ceruloplasmin; Penicillamine; Zinc acetate DOI: 10.3329/bmj.v39i2.7038 Bangladesh Medical Journal 2010, 39(2) pp.50-52